North Arcot and the green revolution - Ramasamy, C.; Hazell, Peter B. R.; Aiyasamy, P. K. (International Food Policy Research Institute, 1991)
North Arcot district which embraces the study region, lies in the northwest of Tamil Nadu state. It is a relatively densely populated region; in 1981 the population density was 357 persons per square kilometer of land. It is also a relatively poor region within India. For example, in 1980/81 the district's net domestic product (NDP) at factor cost was Rs 3,285 million, or Rs 750 (US$95) per capita. This compared with a national average in 1983 of US$260 per capita (World Bank 1986).